MAFG-driven osteosarcoma cell progression is inhibited by a novel miRNA miR-4660 - Hua-jian Shan; Lun-qing Zhu; Chen Yao; Zhi-qing Zhang; Yuan-yuan Liu; Qin Jiang; Xiao-zhong Zhou; Xiao-dong Wang; Cong Cao (Elsevier, 2021)
Osteosarcoma (OS) is the most common primary bone malignancy in the adolescent population. MAFG (v-maf avian musculoaponeurotic fibrosarcoma oncogene homolog G) forms a heterodimer with Nrf2 (NF-E2-related factor 2), binding to antioxidant response element (ARE), which is required for Nrf2 signaling activation. We found that MAFG mRNA and protein expression is significantly elevated in human OS tissues as well as in established and primary human OS cells. In human OS cells, MAGF silencing or knockout (KO) largely inhibited OS cell growth, proliferation, and migration, simultaneously inducing oxidative injury and apoptosis activation. Conversely, ectopic overexpression of MAFG augmented OS cell progression in vitro. MicroRNA-4660 (miR-4660) directly binds the 3' untranslated region (UTR) of MAFG mRNA in the cytoplasm of OS cells. MAFG 3' UTR luciferase activity and expression as well as OS cell growth were largely inhibited with forced miR-4660 overexpression but augmented with miR-4660 inhibition. In vivo, MAGF short hairpin RNA (shRNA) or forced overexpression of miR-4660 inhibited subcutaneous OS xenograft growth in severe combined immunodeficient mice. Furthermore, MAFG silencing or miR-4660 overexpression inhibited OS xenograft in situ growth in proximal tibia of the nude mice. In summary, MAFG overexpression-driven OS cell progression is inhibited by miR-4660. The miR-4660-MAFG axis could be novel therapeutic target for human OS.